Political Meaning of Stasys Šalkauskis’ Philosophy of Culture - Jokubaitis, Alvydas; Jokubaitis, Linas (Politologija, 2020)
The philosophy of culture put forward by Šalkauskis is a version of political philosophy. By using a typology of the relationship between philosophy and democracy we attempt to prove that his philosophy of culture encompasses not one but few different understandings of the relationship between democracy and philosophy. By comparing the ideas of Šalkauskis with the issues of contemporary political philosophy we can see that democracy today is developing by distancing itself from the principles that Šalkauskis presented in his philosophy of culture. The philosophy of culture as developed by Šalkauskis has two distinctive features. First of all, Christianity is interpreted through the matrix of culture and this is why it becomes compatible with democracy. Secondly, philosophy of culture is consciously transformed into ideology and this transformation is what allowed it to become an important factor in political discussions.